Intention of Muslim Stuff Purchase Electronically of Shopping Orientation, Online Trust and Ease of Use (Study on Shopee Barakah App Features) - Hussein, Rifki; Sardiana, Anna (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This study aims to examine the influence of shopping orientation, online trust and ease of use on the online purchase interest of Muslim products through Shopee Barokah application features. The population in this study are followers of the Shopee Instagram account (@shopee_id), both those who have or not yet using Shopee Barokah application feature to purchase Muslim products through online. The research samples are 120 respondents who were determined by using purposive sampling technique. The primary data on this study was collected through a questionnaire and answered by the respondents. The hypothesis test of this study used multiple linear regression. The result of this study indicate that the three independent variables partially and simultaneously have positive influence towards online purchase intention of muslim products through Shopee Barokah application features. Among the three of independent variables, ease of use variable has greater influence than shopping orientation and online trust.